Determinants of foreign direct investment in BRICS- does renewable and non-renewable energy matter?. (May 2021) - Azam, Muhammad; Haseeb, Muhammad
Abstract: The prime objective of the current research is to investigate factors affecting foreign direct investment (FDI) inflows into BRICS countries with a special focus on energy impact on FDI inflows from 1990 to 2018. The empirical results of pane fully modified ordinary least squares (F.M.O.L.S.), dynamics ordinary least squares (D.O.L.S.), Cross-sectional autoregressive distributed lag estimators (CS-ARDL), Augmented Mean Group estimator (AMG), and Common Correlated Effects Mean Group Estimator (CCEMG) exhibits that all variables have statistically positive, while inflation rate has negative effect on FDI. The long-run results suggest that both types of energy utilization (i.e., renewable & non-renewable) are positively contribute to FDI inflows. In terms of magnitude, the effect of renewable energy utilization is higher as compared to non-renewable energy utilization on FDI. Moreover, market size (GDP), trade, and tourism are the key driver of FDI inflows. In contrast, economic de-stability measured through inflation rate discourages FDI inflows into BRICS countries. These findings recommend that the legislature of BRICS countries need to extend the global and national plan to manage the FDI inflows, but it also needs to increase the utilization of renewable energy in the BRICS region and thereby bolster social welfare. Highlights: We explore the role of energy use in the determining FDI inflows in BRICS. We implement the methods of F.M.O.L.S., D.O.L.S., CS-ARDL, AMG, and CCEMG and panel Granger causality test. Empirical estimates reveal that renewable and non-renewable energy are the key determinants of FDI inflows. Market size, trade, and tourism are also the key driver of FDI, while inflation rate deters FDI into the BRICS countries.